Sanksi Berat Bagi Pelaku Korupsi dalam Perspektif Maslahah Mursalah - Mahmudin Hasibuan; Try Sutrisno; Nurfitryani Siregar (Dirosah Islamiyah, 2026)
This study aims to examine the sanctions imposed on perpetrators of corruption according to Islamic law and to analyze the relevance of these sanctions in achieving public welfare and social benefit (maslahah). The research employs a library research method by examining various Islamic legal sources, scholarly opinions, and relevant literature concerning corruption and criminal sanctions. The findings reveal that corruption is categorized as a ta'zir offense in Islamic law, allowing authorities to determine appropriate punishments based on the severity of the crime. Corruption is often associated with al-ghulul, namely the betrayal or embezzlement of public assets. Islamic legal scholars propose sanctions ranging from dismissal from office, imprisonment, confiscation of assets, and, in severe cases, the death penalty. Muhammadiyah scholars further equate corruption with hirabah due to its destructive impact on society and state finances, referring to Surah Al-Ma’idah verse 33 as the legal basis for severe sanctions. The study also emphasizes that effective anti-corruption measures should include moral and spiritual development, fostering awareness of accountability before God and the consequences of unlawful wealth. Islamic teachings warn that acts of corruption lead to severe punishment in the Hereafter and that charitable deeds funded through corrupt wealth are not accepted. Therefore, strict legal sanctions and moral education are considered essential for preventing corruption and promoting justice